Impact of body composition and genotype on haemodynamics during surgery for pheochromocytoma and paraganglioma. Issue 6 (6th September 2022) - Pang, Yingxian; Li, Minghao; Jiang, Jingjing; Chen, Xiang; Fu, Yan; Wang, Cikui; He, Yao; Zhao, Yuanzhe; Wang, Yong; Guan, Xiao; Zhang, Liang; Xu, Xiaowen; et al.
Abstract: Background: Maintaining intraoperative haemodynamic stability can reduce cardiovascular complications during surgery for pheochromocytoma and paraganglioma (PPGL). Risk factors such as tumour size and catecholamine levels are reported to predict haemodynamic responses during surgery for PPGL. We hypothesized that additional factors including body composition and genetic information could further improve prediction. Methods: Consecutive patients with PPGL confirmed by surgical pathology between June 2010 and June 2019 were retrospectively included. Cross‐sectional computed tomography images at the L3 level were used to assess body composition parameters including skeletal muscle area and visceral fat area. Next‐generation sequencing was performed using a panel containing susceptibility genes of PPGL. Differences in clinical‐genetic characteristics and body composition parameters were analysed and compared in patients with and without intraoperative haemodynamic instability (HDI). Results: We included 221 patients with PPGL (median age 47 [38–56] years, and 52% male). Among them, 49.8% had Cluster 2 mutations (related to kinase signalling pathways), 44.8% had sarcopenia, and 52.9% experienced intraoperative HDI. Compared with patients without HDI, more patients with HDI had Cluster 2 mutations (59.8% vs. 38.5%, P  = 0.002) and less had sarcopenia (35.9% vs. 54.8%, P  = 0.005). Multivariate analysis showed that urine vanillylmandelic acid ≥ 58 μmol/day (adjusted odds ratio [OR] = 1.840, 95% confidence interval [CI] = 1.012–3.347, P  = 0.046), tumour size ≥ 4 cm (adjusted OR = 2.278, 95% CI = 1.242–4.180, P  = 0.008), and Cluster 2 mutations (adjusted OR = 2.199, 95% CI = 1.128–4.285, P  = 0.021) were independent risk factors for intraoperative HDI, while sarcopenia (adjusted OR = 0.475, 95% CI = 0.266–0.846, P  = 0.012) decreased the risk. Conclusions: Body composition and genotype were associated with intraoperative haemodynamics in patients with PPGL. Our results indicated that inclusion of body composition and genotype in the overall assessment of patients with PPGL helped to predict HDI during surgery, which could assist in implementing preoperative and intraoperative measures to reduce perioperative complications.